INVESTIGASI NUMERIK PENGURANGAN GAYA DRAG PADA PIPA ENGINE OIL COOLER NUMERICAL INVESTIGATION OF DRAG FORCE REDUCTION ON THE ENGINE OIL COOLER TUBE - Gunawan Sakti; Surya Cakra; Bambang Junipitoyo (Politeknik Penerbangan Surabaya, 2019)
The effort to reduce the drag force on a cylinder is a research that is still popularly carried out by many researchers today. This reduction of drag force is very useful and widely used in the design of heat exchanger pipes, offshore construction piles and bridge piles. This drag forces reducing were carried out using Ansys Fluent® numerical simulation with the geometry of the main cylinder being D = 60 mm, the diameter of the cylinder bluff body d = 0.5D, given the variation of the distance between the center points between the two cylinders is 1.2≤s / D≤1.4 and the Reynold number Re = 5.3 x 104 at free stream velocity U ͚ = 14 m / s. This numerical simulation is also given the turbulent variation of the k-epsilon (2eq), k-omega (2eq) transition model and the k-kl-omega (3eq) transition to obtain numerical simulation results that are close to experimental data. The results of this research are expected to show better aerodynamic performance improvements. The analysis is carried out by comparing several measuring parameters between a single cylinder without disturbance and a cylinder with a disturbance. Some of the considerations used in this aerodynamic performance analysis are Cp, pressure distribution on the main cylinder wall, Cd, Cl and visualization of velocity and pressure contours.